Prime‐time abortion on Grey's Anatomy: What do US viewers learn from fictional portrayals of abortion on television?. Issue 1 (21st September 2021) - Sisson, Gretchen; Walter, Nathan; Herold, Stephanie; Brooks, John J.
Abstract: CONTEXT: Entertainment television can impact viewers' knowledge, attitudes, and reproductive health behaviors, yet little research has examined the impact of scripted abortion plotlines on viewers' abortion knowledge or social supportiveness for those having abortions. We examined the impact of an abortion storyline from Grey's Anatomy on US‐based viewers. METHOD: We conducted an online survey of likely Grey's Anatomy viewers prior to the episode's airing, assessing abortion ideology, knowledge, and support. After airing, we resurveyed respondents (including both those who had and had not viewed the target episode). We tested three hypotheses: episode exposure would (1) improve abortion knowledge and (2) increase support for medication abortion and decrease support for self‐induced abortion, and (3) the effects on knowledge and supportive intention would be moderated by state support for abortion. We used independent samples t tests to examine hypotheses 1 and 2 and PROCESS macro to test the moderated effects (hypothesis 3). RESULTS: The results of the pretest/posttest analysis indicated that exposure to the episode significantly improved medication abortion knowledge. Increases in medication abortion knowledge were tied to explicit educational dialogue and did not translate into an increase in general abortion knowledge or social supportiveness. Notably, abortion‐related state policy significantly moderated the influence of exposure for respondents in states with policies favorable to abortion access. CONCLUSIONS: These findings suggest that entertainment television can contribute to meaningful increases in viewers' knowledge about abortion, but that the potential for impact of entertainment‐education is closely linked to episode content and moderated by state‐level abortion policy.